TREADMILL GENERATOR POWER ANALYSIS DUE TO SPEED AND TIME CHANGES - Gress Ficky Malindo; Jaja Miharja (PT Altin Riset Publishing, 2026)
The increasing global demand for electricity and the depletion of fossil fuel reserves have intensified the need to develop renewable and environmentally sustainable energy sources. One promising alternative is the utilization of human kinetic energy generated during physical exercise. This study investigates the potential of a manual treadmill as a micro-scale electricity generation system by converting kinetic energy into electrical energy through a direct current (DC) generator. The research aims to analyze the electrical power output produced under different treadmill operating conditions and to evaluate the feasibility of this system as an alternative renewable energy source. An experimental method was employed by testing three treadmill speed variations (10 km/h, 20 km/h, and 40 km/h) and three operating durations (15, 30, and 45 minutes). The measured parameters included generator rotational speed, output voltage, electric current, electrical power, and the amount of energy stored in a 12 V/5 Ah battery. The findings indicate that increasing treadmill speed significantly improves voltage, current, and power output, resulting in greater electrical energy storage. However, prolonged operation leads to a gradual decrease in current output due to human physical fatigue, which affects the stability and efficiency of energy conversion. Overall, the study demonstrates that a manual treadmill has considerable potential as a renewable micro-power generation system for low-power electrical applications, emergency electricity supply, and sustainable energy development, while promoting environmentally friendly utilization of human-generated kinetic energy.